Scapular Angiomatoid Fibrous Histiocytoma with EWSR1-CREB1 Fusion in an Adult Patient - Hiroshi Kobayashi; Naohiro Makise; Aya Shinozaki-Ushiku; Yuki Ishibashi; Masachika Ikegami; Shinji Kohsaka; Tetsuo Ushiku; Katsutoshi Oda; Kiyoshi Miyagawa; Hiroyuki Aburatani; Hiroyuki Mano; Sakae Tanaka (Case Reports in Orthopedics)
Background. Angiomatoid fibrous histiocytoma (AFH) is a rare intermediate malignant tumor that arises mainly in soft tissues, especially in the superficial extremities of patients younger than 30 years. There have been a few reports of AFH arising from sites other than soft tissue, including bone, and unusual site and age make it difficult to diagnose this rare tumor. Case Presentation. Here, we present a case of a 54-year-old man who was examined for chest pain, and computed tomography (CT) incidentally detected a bone tumor at the scapula with destruction of cortical bone and invasion into soft tissue. Magnetic resonance imaging revealed multiple cystic components with fluid-fluid levels. FDG-PET showed uptake at the axillary lymph node. The CT-guided needle biopsy revealed spindle cell sarcoma on histopathology. After neoadjuvant chemotherapy, a scapulectomy was performed. The final postresection histopathological diagnosis was the same as the preoperative diagnosis, and no obvious chemotherapeutic effect was observed. Next-generation sequencing of RNA isolated from paraffin-embedded tumor tissue revealed that these lesions harbored the EWSR1-CREB1 fusion gene, and the tumor was diagnosed as AFH. C-reactive protein level, which was elevated preoperatively, decreased after the operation, and there was no recurrence or metastasis 5 years after the treatment. Conclusion. The diagnosis of AFH is difficult when the tumor has an atypical presentation. Comprehensive genomic analysis, especially RNA sequencing, is efficient in diagnosing this rare tumor. Moreover, magnetic resonance imaging findings identical to AFH in soft tissue, the presence of paraneoplastic symptoms such as elevated inflammatory markers, and lymph node swelling were clues towards suspecting this tumor.